한국 연안산 단세포성 수소생산 남세균 종주들의 분류계통, 색소함량 및 최적성장 환경 - 박종우; 김주희; 조애라; 정연덕; 김평중; 김형섭; 이원호; PARK, JONG-WOO; KIM, JU HEE; CHO, AE-RA; JUNG, YUN-DUK; KIM, PYOUNG JOONG; et al. (Pada (Hanʼguk Haeyang Hakhoe), 2015)
To set up unicellular cyanobacterial strains with photo-biological $H_2$ production potential, live samples were repeatedly collected from 68 stations in the coastal zone of Korea for the four years since 2005. Among 77 cyanobacterial strains established six (KNU strains, CB-MAL002, 026, 031, 054, 055 and 058) were finally chosen as the excellent strains for $H_2$ production with $H_2$ accumulation over 0.15 mL $H_2\;mL^{-1}$ under general basic $H_2$ production conditions as well as positive $H_2$ production for more than 60 hr. To explore optimum procedures for higher $H_2$ production efficiency of the six cyanobacterial strains, the inter-strain differences in the growth rate under the gradients of water temperature and salinity were investigated. The maximum daily growth rates of the six strains ranged from 1.78 to 2.08, and all of them exhibited $N_2-fixation$ ability. Based on the similarity of the 16S rRNA sequences, all the test strains were quite close to Cyanothece sp. ATCC51142 (99%). The six strains, however, were grouped into separate clades from strain ATCC51142 in the molecular phylogeny diagram. Chlorophyll- a content was 3.4~7.8% of the total dried weight, and the phycoerythrin and phycocyanin contents were half of those in the Atlantic strain, Synechococcus sp. Miami BG03511. The growth of the six strains was significantly suppressed at temperatures above the optimal range, $30{\sim}35^{°}C$, to be nearly stopped at $40^{°}C$. The growth was not inhibited by high salinities of 30 psu salinity in all the strains while strain CB055 maintained its high growth rate at low salinities down to 15 psu. The euryhaline strains like CB055 might support massive biotechnological cultivation systems using natural basal seawater in temperate latitudes. base seawater. The biological and ecophysiological characteristics of the test strains may contribute to designing the optimal procedures for photo-biological $H_2$ production by unicellular cyanobacteria. 광생물학적 수소생산 잠재력을 가진 한국산 단세포성 남세균 단종배양체를 확립하기 위하여, 2005부터 4년 동안 우리나라 연근해역의 68개 정점에서 반복적으로 시료를 채집하였다. 확보된 77개 종주의 단종배양체 가운데 6개 종주(KNU CB-MAL002, 026, 031, 054, 055, 058)는 일반적인 수소생산 조건에서 0.15 mL $H_2\;mL^{-1}$ 이상의 수소 누적량을 나타내었고, 60시간 이상의 수소 지속생산을 기록하였다. 6개 실험 종주의 수소생산을 더욱 높여주는 최적의 공정을 규명하기 위한 연구의 일환으로, 각 종주의 수온 및 염분 등급 별 성장도를 측정하여, 종주 간의 차이(interstrain difference)를 비교 하였다. 실험 종주 6개의 일일 최대 성장률은 1.78~2.08 범위로 높았고, 모든 실험 종주가 질소고정능을 나타내어, 광생물학적 수소생산 잠재력이 높은 것으로 예상되었다. 16S rRNA 분석결과, 실험 종주 들은 Cyanothece sp. ATCC51142와 높은 유사도(99%)를 보였으나, 6개의 종주 모두가 분자계통도에서는 ATCC51142와 서로 다른 clade에 별도로 나뉘어져, 본 실험 종주의 일부는 신종일 가능성이 있다. 엽록소-a는 건중량 대비 함유량이 3.4~7.8%의 범위로 나타났으며, 보조색소인 홍조소와 남조소의 함유량은 대서양산 남세균 Synechococcus sp. Miami BG03511의 절반 수준이었다. 최적 성장온도로 확인된 $30{\sim}35^{°}C$ 구간 밖의 온도에서는 성장이 크게 제한되었으며, $40^{°}C$의 고온에서는 모든 실험종주의 성장이 거의 정지됨을 확인하였다. 실험 종주들은 30 psu의 염분에서 성장이 우세하였다. 이 가운데 CB055 종주는 15 psu까지의 상대적 저염 구간에서도 높은 성장을 유지하여, 염분의 변동에 대한 내성이 높은 종주로 확인되었다. 이와 같은 광염 특성의 종주는 연안수의 계절적인 염분변화가 상대적으로 큰 온대 연안역에서 이 종주를 생물공학적으로 응용하게 될 경우, 기반해수의 계절적인 염분 변화에도 불구하고 배양 공정상의 높은 유연성을 나타내게 될 것이다. 본 연구 결과 규명된 각 종주 별 생리적 특성 자료는 향후 광생물학적 수소생산 최적공정을 확립하기 위한 모델연구에 긴요할 것이다.